Paleo-Typhoon Events as Indicated by Coral Reef Boulder Deposits on the Southern Coast of Hainan Island, China - Zhou, Liang; Gao, Shu; Jia, Jianjun; Yang, Yang; Tong, Changliang; Wang, Aijun (Frontiers in Marine Science, 2021)
The southern coast of Hainan Island, China, is one of the most frequently hit areas of tropical cyclones in the Northwest Pacific regions. Although some of the extreme typhoon events were known in historical times, quantitative information on the timing and magnitude of paleo-typhoon events in this coastal area remains rare. In the present study, a large number of coral reef boulders were found on the Xiaodonghai reef platform, on the south coast of Hainan Island. Morphometric analysis of the boulders shows an exponentially ﬁning landward trend, indicating a storm origin; a wave-induced current velocity of 2.41–5.71 m/s during the storm events is required to transport the boulders that were originally situated outside the reef edge. Based on the U/Th and 14C dating for the age-indicating samples taken from the boulders, seven major periods with intense typhoon activities were identified, for the last 4000 years, i.e., 1800–1500 BCE, 1200–900 BCE, 50–120 CE, 550-800 CE, 900-1000CE, 1350–1900CE, and 1910–2000 CE. A comparison with the regional typhoon records in terms of climatic parameters in the northwestern Pacific and South China Sea regions indicates that the longitudinal variations of intense typhoon frequency was mainly controlled by ENSO, dominately modulated by the Intertropical Convergence Zone. Because of the future warming climate, there will be a trend of enhanced typhoon risk for the southern Hainan Island coasts.